The Effect of the Use of Organic Fertilizers Made from Industrial Waste on Beniazuma Sweet Potatoes under Different Plant Spacings - Ayutyas Sayekti; Prima Gandhi; Agief Julio Pratama (Unversitas Muhammadiyah Mataram, 2026)
Sweet potato productivity is largely determined by agronomic practices, particularly plant spacing and nutrient management. However, excessive reliance on chemical fertilizers may negatively affect soil sustainability. Therefore, alternative nutrient sources derived from industrial waste are increasingly explored within the framework of sustainable agriculture and circular resource utilization. This study aimed to evaluate the growth and yield performance of Beniazuma sweet potato under different fertilizer treatments and plant spacing arrangements. The experiment was conducted in Dramaga, Bogor Regency, Indonesia, from June to December 2022 using a factorial randomized complete block design. Two plant spacing levels (40 cm × 40 cm and 60 cm × 60 cm) and six fertilizer treatments (control, NPK, milk waste-based organic fertilizer, and compost at different doses) were applied. Observed variables included tuber number, tuber weight, and shoot biomass. Data were analyzed using analysis of variance followed by the LSD test at the 5% level. The findings revealed that plant spacing had a stronger influence on yield components compared to fertilizer treatments. Wider spacing (60 cm x 60 cm) increased tuber weight up to 0.3 kg/plant compared to 0.1–0.2 kg at closer spacing. Organic fertilizers derived from industrial waste performed comparably to inorganic fertilizers, indicating their feasibility as sustainable nutrient sources in sweet potato cultivation.